2012
DOI: 10.3174/ajnr.a2870
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Correlation of a New MR Imaging Method for Assessing Lumbar Foraminal Stenosis

Abstract: BACKGROUND AND PURPOSE:Recently, Lee et al reported a new grading system for the lumbar spinal foraminal stenosis. They considered the type of stenosis, the amount of fat obliteration, and the presence of nerve root compression. Our aim was to evaluate whether a new MR imaging grading system correlated with symptoms and neurologic signs and could replace the previous grading system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 6 publications
(6 reference statements)
2
23
0
Order By: Relevance
“…A second limitation was the single posture used for C-spine MRI, as the C-spine posture affects the dimensions of the neural foramen [10]. Bartlett et al [11] reported that cervical neural foramina are more likely to appear abnormal if the spine is extended and the foramina become narrowed.…”
Section: Discussionmentioning
confidence: 99%
“…A second limitation was the single posture used for C-spine MRI, as the C-spine posture affects the dimensions of the neural foramen [10]. Bartlett et al [11] reported that cervical neural foramina are more likely to appear abnormal if the spine is extended and the foramina become narrowed.…”
Section: Discussionmentioning
confidence: 99%
“…4 Semi-quantitative methods help eliminate factors leading to variability caused by internal subjective standards. 10 In comparison with previous reports, our study reveals similar CNFS distributions of each grade, according to each grading system (Table 1). 4,5 In the Park system, .70% of patients were Grade 0 (68% in the previous study, Park et al 4 ) and in the Kim and mKim systems, between 56% and 72% of patients were Grade 0 (53-72% in previous studies, Park et al 5 ).…”
Section: Discussionmentioning
confidence: 36%
“…Day-to-day as well as diurnal change of the intra-individual disc height and volume have been described in the literature [9,15,16] and could have contributed to the fact, that we had 10 (4.2 %) individuals with nerve root contact to disc material in the 3 T scan but not in corresponding 1.5 T images. Varying personal activities before and MRI scanning at different times of the day can be other reasons for minor mismatches between disc and nerve root classification in 1.5 and 3 T images.…”
Section: Discussionmentioning
confidence: 83%
“…A severity grading system for lumbar nerve root compromise within the spinal canal and/or neuroforamen was applied as published by Pfirrmann and coworkers [7]: Grade 0 (normal-no compromise), Grade 1 (contact-there is visible contact of disc material with the nerve root), Grade 2 (deviation-the nerve root is displaced by disc material), Grade 3 (compression--the nerve root is compressed between disc material and the wall of the spinal canal). Lee et al's grading system was used to assess lumbar foraminal stenosis [8,9] Axial ADC maps and coronal, and sagittal reformatted DWI images were used to identify the appropriate level and side of a particular nerve root and its ganglion. Using ImageJ 1 axial ADC maps and coronal reformats were analyzed to obtain the following bilateral linear measurements within axial ADC maps at the lumbar spinal levels (L1-S1): length of dorsal root ganglia (DRG) (mm), and width of DRG (mm).…”
Section: Methodsmentioning
confidence: 99%